Linking Technology Readiness and eWOM Readiness: Evidence from Indonesian MSMEs - Fadlullah, Fauzan; Nuha Ilmawan, Faiz (Journal of Economics and Social Sciences (JESS), 2025)
Electronic Word of Mouth (eWOM) has become a central factor influencing consumer behavior in the digital economy, yet many micro, small, and medium enterprises (MSMEs) remain unprepared to manage it effectively. While prior studies have applied the Technology Readiness Index (TRI) in areas such as e-commerce and customer relationship management, little is known about its role in shaping organizational readiness for eWOM. This study addresses this gap by exploring how the four TRI dimensions—optimism, innovativeness, discomfort, and insecurity—affect eWOM readiness among Indonesian MSMEs. A quantitative survey was conducted, and the data were analyzed using structural equation modeling to capture the relationships between constructs. The findings confirm that technology readiness significantly influences MSMEs’ ability to engage with eWOM, with positive dimensions acting as drivers and negative dimensions serving as barriers. The study extends TRI theory into the underexplored domain of digital customer engagement and highlights the need for MSMEs to develop structured processes and managerial capabilities to leverage eWOM strategically. Policy initiatives such as UMKM Go Digital are encouraged to move beyond platform adoption and strengthen support for review management practices. Limitations of the study include its cross-sectional design and single-country focus, suggesting future comparative and longitudinal research.